2020
DOI: 10.3390/su12031095
|View full text |Cite
|
Sign up to set email alerts
|

Tourists and Local Stakeholders’ Perception of Ecosystem Services Provided by Summer Farms in the Eastern Italian Alps

Abstract: In the Alps, summer farms are temporary units, where cattle are moved during summer to graze on Alpine pastures, which provide multiple ecosystem services (ESs), many of which do not have a market value. This study aimed at understanding and comparing the perceptions of summer farms and of the associated ESs by local stakeholders and tourists in a study area of the province of Trento in the eastern Italian Alps. Thirty-five online questionnaires and two focus groups were realized with local stakeholders involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
1
18
0
2
Order By: Relevance
“…Overall, both cheeses achieved good consumer acceptability, obtaining average liking scores ranging from 6.0 to 7.3. These results confirm what previous studies have stated, even without a real product tasting, as the quality of dairy products is an important aspect for both tourists and local farmers in the perception of summer mountain farms [ 3 , 20 ]. The significant effect of the product found for the whole panel (first row of Table 7 ) demonstrated that pasture cheese was significantly preferred over the stall one.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, both cheeses achieved good consumer acceptability, obtaining average liking scores ranging from 6.0 to 7.3. These results confirm what previous studies have stated, even without a real product tasting, as the quality of dairy products is an important aspect for both tourists and local farmers in the perception of summer mountain farms [ 3 , 20 ]. The significant effect of the product found for the whole panel (first row of Table 7 ) demonstrated that pasture cheese was significantly preferred over the stall one.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have focused on the effects of summer grazing on dairy product characteristics, demonstrating that mountain products are different from indoor feeding products, in terms of sensory attributes [ 9 , 10 , 11 , 12 , 13 ], volatile organic compounds (VOCs)’ profile [ 8 , 14 , 15 , 16 ], and fatty acid composition [ 11 , 17 , 18 ]. The quality of dairy mountain products is also a key aspect for consumers [ 19 ], for whom the production of high-quality dairy products is the most important ecosystem service among those provided by summer farms [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is important, as it facilitates the creation of joint projects to develop and promote cheese, as demonstrated by Torre [6] in the case of Comté cheese, and De Roest and Mangi [54] in the case of Parmigiano Reggiano cheese. In addition, coordination between producers and actors in the tourism sector seems to be crucial in increasing awareness of high-quality cheeses [36]. However, trust toward the provincial government and municipal authorities was at some of the lowest levels, even though their values were around 7.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen dairy cooperatives comprising 729 farmers are currently associated to the consortium. The cooperatives process approximately 80% of the milk produced in the province (120,000 tons a year) [36]. In 2018, the Primiero cooperative paid the highest price of all 17 associated cooperatives to its members: €0.66/kg [37].…”
Section: Territorial Proximity As a Means Of Deepening Understanding mentioning
confidence: 99%
“…During the last decades, in the European mountain areas the traditional livestock systems based on extensive management of pastures and meadows have been strongly affected by two processes: intensification of farmland and herds management in suitable areas and abandonment in marginal areas [18,19]. As a result, mountain agroecosystems have been profoundly altered, with either a conversion to arable crops and intensification of farmland management or reforestation of abandoned grasslands [14,20], with the resulting loss of the associated ES [10,21,22], which, although non-marketable, are highly valued by society [11,23] such as the maintenance of pasture and meadows guaranteed by animals' grazing. The main factors determining abandonment are family constraints, topographic and climatic conditions, economic and social elements [24,25] since, for example, farming profitability is lower and not sufficient for the families' sustenance.…”
Section: Introductionmentioning
confidence: 99%